PENGEMBANGAN SISTEM MANAJEMEN KARAKTER SEKOLAH MELALUI PROGRAM KARSA PADA SEKOLAH DASAR BINAAN DI KECAMATAN KROYA - Dwi Angga Ningsih; Wildan Nurul Fajar; Ratna Susi Riyanti (STKIP Subang, 2026)
Character education strengthening underpins this study, as its implementation in elementary schools continues to face challenges related to systematic, data-based, and sustainable management. This study aimed to describe the initial implementation of the KARSA Program (Reflective Character, Voice, and Action), analyze early changes in teachers’ practices, school culture, and students’ character, and identify supporting and inhibiting factors in the program implementation. This qualitative study employed a case study design involving 13 elementary schools under the Muhammad Syafei Cluster in Kroya District, Cilacap Regency. The informants included 13 principals, 109 teachers, members of the School Character Team, and students. Data were collected through observation, interviews, documentation, and program monitoring records. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The findings showed that the KARSA Program developed a school character management system through the establishment of School Character Teams, data-based principal leadership strengthening, In-House Training on Character Management, the development of character standard operating procedures, character portfolios and dashboards, as well as reflection activities and the strengthening of student voice. Early changes were evident in increased teacher reflective practices, the use of character journals, and observations of student behavior. School culture shifted toward a more systematic, collaborative, and data-based approach to character education management. Students demonstrated initial development in responsibility, social awareness, self-reflection, and initiative. Supporting factors included principals’ commitment, an established culture of character habituation, teacher training, the use of character data, and school community collaboration. Obstacles included variations in teachers’ competence in facilitating reflection, limited time, administrative workloads, limited mentoring, and uneven family support.